2023
DOI: 10.37811/cl_rcm.v7i1.4843
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 y su impacto en hábitos de consumo alimentario en estudiantes universitarios del estado de Veracruz

Abstract: El confinamiento derivado de la COVID-19 tuvo un impacto negativo en múltiples aspectos de la vida humana. En niños y adolescentes, se ha vinculado con cambios de comportamiento, incluyendo variaciones en el consumo alimentario y frecuencia de actividad física. Objetivo: detectar y describir cambios en la conducta alimentaria de estudiantes universitarios durante la pandemia de Covid-19, para ello se llevó a cabo un estudio no experimental, de tipo transversal, descriptivo, con 653 alumnos de la Universidad Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…While Ortiz et al ( 36 ), in an investigation carried out in Chiapas, Mexico, with university students, observed an increase in the consumption of meals with an increase in processed meats, cookies or pastries, and sugary drinks, the consumption of fruits and vegetables decreased without this being significant. For Reyes Diaz et al ( 37 ), in a study carried out with university students in Veracruz, Mexico, it was found that physical activity decreased, a fact that could be related to weight gain, while the consumption of fruits, vegetables, and legumes had ambivalent results.…”
Section: Discussionmentioning
confidence: 99%
“…While Ortiz et al ( 36 ), in an investigation carried out in Chiapas, Mexico, with university students, observed an increase in the consumption of meals with an increase in processed meats, cookies or pastries, and sugary drinks, the consumption of fruits and vegetables decreased without this being significant. For Reyes Diaz et al ( 37 ), in a study carried out with university students in Veracruz, Mexico, it was found that physical activity decreased, a fact that could be related to weight gain, while the consumption of fruits, vegetables, and legumes had ambivalent results.…”
Section: Discussionmentioning
confidence: 99%
“…Para Reyes et al (2023), la evaluación del consumo de alimentos se convierte en un componente crucial para comprender estos patrones alimentarios.…”
Section: Capítulo IIunclassified
“…Hallándose a nivel global que no hay diferencia en todos los ítems menos para los casos de alimentos procesados, fritos y horneados. Mientras queReyes et al (2023) reportan el aumento de consumo de 5 a 6 veces por semana de alimentos frescos como frutas y verduras en un 14% y 3% respectivamente Monteverde et al (2022). manifiestan que un 19% de sus encuestados durante el período de aislamiento social consumieron más alimentos procesados, en nuestro caso no se observa en el IMC diferencia significativa.…”
unclassified